PENGARUH DAYA TARIK WISATA, FASILITAS WISATA, DAN KEAMANAN TERHADAP LOYALITAS WISATAWAN PADA WISATA SUNGAI TROKON CURUP KABUPATEN REJANG LEBONG - Aldino, Fikal Rahmad; Bustami, Taufik (UM. Bengkulu, 2024)
The objectives of this study are (1) to find out the influence of tourist attractions on tourist loyalty, (2) to find out the influence of tourist facilities on tourist loyalty, (3) to find out the influence of tourist security on tourist loyalty, and (4) to find out the influence of tourist attractions, tourist facilities, and security on tourist loyalty on tourism in the Trokon Curup River, Rejang Lebong Regency. This type of research is a quantitative research, conducted from November 2023 to January 2024. The population is all visitors to the Trokon Curup River, Rejang Lebong Regency. The sample in this study is tourists who have visited the tour at least 2 times. The respondents in this study amounted to 132 respondents. Data collection using questionnaires and data analysis using a multiple linear regression model and processed using SPSS version 25 software. The results of the study show that tourist attraction has a positive effect on tourist loyalty. Tourist facilities have a positive effect on tourist loyalty. Tourism security has a positive effect on tourist loyalty. Tourist attractions, tourist facilities and tourism safety together affect tourist loyalty, which contributes 61.8% in influencing tourist loyalty in the Trokon Curup River tourism in Rejang Lebong Regency, while the remaining 38.2% is influenced by other variables that are not included in this research model. Keywords: Attractions, Facilities, Security, Tourist Loyalty.